Analysis on the habitat use of bearded pigs in Sarawak - Navennec, Alexia; Cheok, Melynda Ka Yi; Jayasilan, Mohd. Azlan (IUCN, 2016)
Sanctuary, and a High Conservation Value Forest near Bintulu We used infra-red sensor cameras, a non-invasive method to gather information on bearded pigs over large survey areas and for several months at a time. Total of 32 camera-traps including models from Reconyx and Bushnell were used for 36 locations between March 2012 and November 2013. Occupancy analysis using PRESENCE 2.0 shows that Beach forest and Mixed Dipterocarp Forests are more likely to be inhibited, compared to Kerangas (Heath) forest. Additional sampling and effort is needed to further investigate the habitat preference between protected areas by increasing the number of camera trap locations in different habitats.